Pengaruh Media Pembelajaran Interaktif PowerPoint Materi Indonesia Kaya Budaya Terhadap Minat Belajar IPAS Siswa Kelas IV SDN 138 Pekanbaru - Dian Wahyuni; Muhamad Nukman (Jayapangus Press, 2026)
Student learning interest in science learning in elementary schools is still relatively low due to the limited use of interactive and interesting learning media. This study aims to analyze the effect of interactive PowerPoint media based on Indonesian culture on the interest in learning science in grade IV students of SDN 138 Pekanbaru. The study used a quantitative approach with a pre-experimental approach through a one-group pretest-posttest design. The research sample consisted of 37 grade IV students selected using a purposive sampling technique. Data collection techniques were carried out through observation, documentation, and student learning interest questionnaires. The results of the instrument validity test using Aiken's V obtained a value of 0.87 which indicates a very valid instrument. Data analysis used descriptive statistics and paired sample t-test. The results showed that the average student learning interest increased from 45.27 in the pretest to 57.11 in the posttest. The results of the hypothesis test showed a significance value of 0.000 <0.05 with a t value of -17.986, so there is a significant effect of the use of interactive PowerPoint media on students' interest in learning science. Unlike previous research that focused more on digital media in general and cognitive learning outcomes, this study contributes to the development of interactive learning media based on Indonesian culture to increase elementary school students' interest in science. The findings indicate that integrating local culture into digital learning media can increase student engagement and interest in learning in a more contextual and meaningful way.